(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The results of a study of the deformation characteristics of polycrystalline films under one-sided cyclic mechanical stresses are presented. The films were obtained on a polyamide substrate using the method of thermal vacuum condensation of molecular beams and had a columnar porous structure with individual crystalline grain sizes of 2.0–2.5 μm. The influence of static and cyclic deformations on the electrical resistance and volt-ampere characteristics of strain gauge films was studied with the aim of producing strain gauges for fatigue damage accumulation based on them. It has been shown that at room temperature, such films exhibit high static strain sensitivity relative units and a significant hysteresis in resistance changes is observed with a small number of cycles of alternating deformations.